Effectiveness of Brazilian Educational Connectivity Policies: Identification of Obstacles from Past Experiences and Recommendations for the Future (Law, State and Telecommunications Review, 2024)
[Purpose] This article suggests the creation of a new normative tool to overcome the lack of connectivity among public school students and the elderly population, notably those who live on the outskirts of urban centers and in geographically isolated regions.[Methodology] An exploratory and bibliographical research was carried out in the collections of the Brazilian Institute of Geography and Statistics and the National Telecommunications Agency, whose data is stratified. The central objective was to identify the obstacles that stood in the way of the elaboration and execution of public policies aimed at the equitable expansion of telecommunications accessibility in the country. As a theoretical contribution, the option was for studies relating to the following topics: public policies, public telecommunications policies, current legislation, the organization of the Education System in Brazil and the elderly population.[Results] It was found that public school students and the elderly population are the segments of the Brazilian population that have faced the greatest difficulties in the telecommunications area in the last three years.[Practical Implications] The creation of the new normative tool, that is, the new proposed public policy, is expected to bring benefits to the population segments (public school students and the elderly population) and to society in general.[Originality] Digital inequality, which affects a significant portion of the population, can be overcome through the implementation of the new normative tool, suggested in this article, which should guarantee expansion and connectivity for isolated populations. The implementation of this proposal will fill the connectivity gaps detected and strengthen democratic principles.Keywords: Public Policies. Public Telecommunications Policies. Education System in Brazil. Population Segments without Connectivity. Suggestion of a new Public Policy.